Loss of Sense of Smell and Taste among Reverse Transcriptase Polymerase Chain Reaction Positive COVID-19 Patients of a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Shah, Rajeev; Koirala, Bipin; Gyawali, Sangya (Birat Journal of Health Sciences, 2021)
Results: A total of 166 patients were included in the study. The age of the patients ranged from 10 to 84 years with a mean age of 44.34 ± 23.059 years. Out of the 166 RT-PCR positive patients 103 (62%) had a loss of taste while 114 (68.7%) had a loss of smell. Nearly half of the subjects about 99 (51.6%) had dysfunction in both taste and smell. Conclusions: The present study shows the strong association between the olfactory and gustatory dysfunction with that of COVID infection. Patients with loss of taste and smell should be evaluated properly at the time of COVID pandemic. Olfactory and Gustatory dysfunction can be the early and only manifestation of COVID infection. The prevalence of loss of smell and taste was similar to other studies done in similar settings.